The Influence of Gadgets on Development Cognition in Early Childhood - Betty, Yensi Yusniati; Amseke, Fredericksen Victoranto (Cognitive Development Journal, 2024)
Cognitive development is the mental ability to process information, think, learn and solve problems. The effect of gadgets on early childhood cognitive development is very important. This is because the rapid development of technology and the increasing use of gadgets among children trigger concerns about their impact on child development and The benefits of this study are to increase parents' and educators' awareness of the impact of gadgets on child development, provide scientific information about the effect of gadgets on children's cognition, and help develop effective educational strategies. This study can also help parents and educators in making decisions about the use of gadgets and improve the quality of education and child development. This study aims to determine the effect of gadget use on early childhood cognitive development at Sabulus Naimata PAUD. The research method applied was descriptive qualitative with a population of 45 children aged 4-6 years. Data collection techniques were interviews and documentation studies. The research participants were one teacher and three parents, as well as document analysis related to the use of gadgets in PAUD. The results of data analysis show that gadget use has a significant influence on early childhood cognitive development. The influence can be positive, such as improving problem-solving skills and creativity, but also negative, such as being easily distracted, less active in playing, and difficulty concentrating. This study concludes that the use of gadgets in early childhood at PAUD Sabulus Fani Naimata has both positive and negative impacts. It is expected that parents and teachers can assist and limit children to use gadgets and balance them with other activities that support children's cognitive development.